Associations between physical activity and heart disease among middle-aged and older Chinese adults - Liu, Yujia; Yuan, Chaoqun; Chen, Tong; Zhou, Linlin; Zhu, Gengyin; Chen, Yu (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo quantify the risk of heart diseases (HD) and determine the relationship between physical activity (PA) dimensions and HD among Chinese middle-aged and older individuals.MethodsUsing data from the China Health and Retirement Longitudinal Study (CHARLS, 2018), 16,927 participants were included in this study. Multivariate logistic regression was performed to determine the association between HD risk and PA dimensions, including volume, intensity, frequency, and duration. Restricted cubic spline analysis was conducted to assess the dose-response relationship between PA and HD risk.ResultsCompared to the least active participants, a low risk of HD was significantly associated with a higher PA volume. With regards to frequency, a lower HD risk was associated with performing vigorous PA except for 3–5 days/week. The frequency and duration of light as well as moderate PA had no significant associations with HD risk after adjusted by using covariates. A non-linear association was also noted, with increased PA being associated with decreased HD risk, with steeper reductions in HD risk at low activity levels than at high activity levels. There was a non-linear association between PA and HD risk in participants in male and aged older than 65 years.ConclusionsAn inverse non-linear dose-response association was detected between the total volume of PA and HD risk. As PA increased to 4,000 METs-min/week, HD risk in the overall population decreased by approximately 26%, while further increases in PA did not produce any further marked reduction in the risk. A vigorous intensity of PA was associated with a reduced risk of HD and is strongly recommended.